Análise do monitoramento pós estudo de impacto ambiental no Estado de São Paulo - Munno, Carolina Milanetto (2005)
This work intented to realize a study about the situation of process of Environmental Impact Assessment (EIA) in São Paulo State, with emphasis in the monitoring pos-EIS (Environmental Impact Statment) phase, that it is essencial for the efficiency and efficacy of EIA. The purpose was to evaluate the frequency that the monitoring is realized, which are the methods used, what the efficiency, the negative points and the difficults to execution of this system. For that, it was realized a bibliography revision about national and internacional practices of EIA, with research at libraries of Secretaria de Meio Ambiente do Estado de São Paulo (SMA), Companhia Estadual de Saneamento Ambiental (CETESB), Departamento de Avaliação de Impacto Ambiental (DAIA) and USP, and researches on data base. It were made interviews with technicals directors of DAIA/SMA and was also elaborated a questioner, that approach some points of EIA practices in São Paulo State. This questioner was sent to professionals of area. The results evidenced that despite of monitoring pos-EIS is very impotant in the context of EIA, it is not executed in the most of the cases. Many failures are pointed out in the process, which results in the non aplication of monitoring pos-EIS. The lack of engagement with the environmental quality and the sustainability, the lack of structure in the environmental agencies, the bureaucratic and consequent slowness of the process, the little participation of community, the difficulty in getting material about the topic, and others are some of factors mentioned. If the procedure were not improved, for assure the accomplishment of terms and commitments defined, as well as the learning with mistakes and the rights of each case, a powerfull instrument of Environmental Policy would be discredited and turn on in one of numerous bureaucratic obstacles that difficult the access on natural resourses of the country, but are not efficient to assure that the improvement happens in benefit of society.